A Review On The Fabrication Techniques Of Aluminium Matrix Nanocomposites - Marini, C. D.; Fatchurrohman, Nanang (Penerbit Universiti Teknologi Malaysia, 2015)
In recent year, metal matrix composites have been considered as materials that offer better mechanical properties compared to conventional alloy. Recently, the developments of metal matrix nanocomposites (MMNCs) have become more attractive in various applications. However, the synthesis of MMNCs by conventional casting method has shown a limitation due to low wettability of the reinforcement phase by the molten metal. This paper is aimed at reviewing the best result techniques to fabricate the aluminium matrix nanocomposite (AlMNCs). However, each of these techniques has their own advantages and disadvantages. This review conclude that the powder metallurgy (PM) as the best technique certainly for mass production and cost effectiveness.